2012
DOI: 10.3109/07357907.2012.657816
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Expression of Axl and Correlation with Invasion and Multidrug Resistance in Cancer Cells

Abstract: Dysregulation of Axl receptor tyrosine kinases is implicated in the pathogenesis of several sensitive and refractory cancers. In this study we showed that Axl expression was upregulated in drug-resistant cancer cells, as compared to those in parental cells. Downregulation of Axl expression by RNAi led to a decrease of K562/ADR and MCF-7/ADR cells invasion, proliferation in soft agar, and increased cells chemosensitivity in vitro. In nude mice bearing xenografts, downregulation of Axl in MDR cells enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…We previously showed that Axl has a crucial role in promoting invasion, lymphatic metastasis, and multidrug resistance . In this study, we identified down‐regulating of Axl not only could effectively regulate the invasiveness, drug resistance of breast tumor cells in vitro , and animal models in vivo , but also related with clinicopathologic characteristics of human breast cancer.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…We previously showed that Axl has a crucial role in promoting invasion, lymphatic metastasis, and multidrug resistance . In this study, we identified down‐regulating of Axl not only could effectively regulate the invasiveness, drug resistance of breast tumor cells in vitro , and animal models in vivo , but also related with clinicopathologic characteristics of human breast cancer.…”
Section: Discussionmentioning
confidence: 78%
“…In the previous studies, we concluded that Axl had a critical role in the PI3K/Akt‐PAK1 signal pathway and knockdown of it inhibits the metastasis properties of hepatocellular carcinoma . We also found that differential expressions of Axl are correlated with invasion and multidrug resistance in cancer cells . Given that Axl may have an important role in tumor metastasis and drug resistance, we have prompted in this study to explore its detailed mechanism in the regulation of tumor invasion and chemosensitivity via PI3K/Akt pathway.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased MER expression is associated with leukemias, lymphomas, melanoma, rhabdomyosarcomas, and gastric and prostate cancers (4)(5)(6). AXL and MER expression also has been directly correlated with poor prognosis in cancer (6)(7)(8)(9). Moreover, ectopic expression of AXL has been shown to confer resistance to EGF receptor therapy in lung cancer (10,11).…”
mentioning
confidence: 99%
“…AXL-depleted murine breast cancer cells with breast cancer stem-cell-like properties were more sensitive to paclitaxel and etoposide compared to AXL-competent cells [17]. Similarly, inhibition of AXL signaling in MCF-7 cells with acquired resistance to conventional chemotherapies restored their sensitivity [91]. In TNBC and NSCLC cells that have undergone an EMT, inhibition of AXL can synergize with antimitotic agents such as docetaxel and paclitaxel but not with gemcitabine, doxorubicin, or cisplatin [92].…”
Section: Conventional Erapiesmentioning
confidence: 99%